Automatic Generation of MCQS from Domain Ontology- A Survey - Serin V. P, Sahana; Rajendran V, Viji (International Journal of Computer Sciences and Engineering, 2018)
Ontologies are knowledge representation structures, that models domain knowledge by concepts, instances, rolesand their relationships. Assessment systems can exploit this knowledge by using multiple choice Questions (MCQs). Online assessment systems are mainly using MCQs instead of subjective questions for conducting the tests. Using MCQs for assessments has merits as well as demerits. For assessing wide range of knowledge, MCQs are used. It is because they require very less administrative overhead as well as provide instant feedback to test takers. There are several ontology based MCQ generation approaches proposed by many authors. These approaches generates different kinds of questions, in one approach the stem of all generated question remains the same, another one make use of the semantics of the domain, represented in the form of TBox axioms andABox axioms, to frame interesting MCQs. Some other methods differ in generating distractors for the questions. There are approaches which controls the difficulty level of generated MCQs. This paper gives a literature review and comparison of some of the methods for MCQ generation from ontology.